Substrate Uptake by Uncultured Bacteria from the Genus Achromatium Determined by Microautoradiography - Gray, N. D. (American Society for Microbiology, 1999)
Microautoradiography was used to investigate substrate uptake by natural communities of uncultured bacteria from the genus Achromatium. Studies of the uptake of (14)C-labelled substrates demonstrated that Achromatium cells from freshwater sediments were able to assimilate (14)C from bicarbonate, acetate, and protein hydrolysate; however, (14)C-labelled glucose was not assimilated. The pattern of substrate uptake by Achromatium spp. was therefore similar to those of a number of other freshwater and marine sulfur-oxidizing bacteria. Different patterns of radiolabelled bicarbonate uptake were noted for Achromatium communities from different geographical locations and indicated that one community (Rydal Water) possessed autotrophic potential, while the other (Hell Kettles) did not. Furthermore, the patterns of organic substrate uptake within a single population suggested that physiological diversity existed in natural communities of Achromatium. These observations are consistent with and may relate to the phylogenetic diversity observed in Achromatium communities. Incubation of Achromatium-bearing sediment cores from Rydal Water with (35)S-labelled sulfate in the presence and absence of sodium molybdate demonstrated that this bacterial population was capable of oxidizing sulfide to intracellular elemental sulfur. This finding supported the role of Achromatium in the oxidative component of a tightly coupled sulfur cycle in Rydal Water sediment. The oxidation of sulfide to sulfur and ultimately to sulfate by Achromatium cells from Rydal Water sediment is consistent with an ability to conserve energy from sulfide oxidation.